VISUAL SUPPORT OF THE TOPIC "ALGORITHMS FOR SORTING AND SEARCHING" COURSE OF BASIC PROGRAMMING - Lvov, Michael; Shishko, Ludmila; Chernenko, Irina; Kozlovsky, Evgen (Journal of Information Technologies in Education (ITE), 2020)
This paper is investigated the requirements and general theoretical approaches to the construction the computer mathematics system for educational purposes of studying algorithmization and programming, which have their own specificity. The basic form of practical activity of the student is laboratory work. Specific problems are the problems of program representation by both special and general mathematical models. It is advisable to carry out the initial studyof algorithmization in the course of informatics of high school using specialized educational-oriented software-methodological software. The article considers a subject-oriented approach to the construction of information systems to support the learning process while studying the course of algorithmization and programming. This approach is applied to the implementation of the software-methodological complex "Video Interpreter for searching and sorting algorithms”. The software-methodical complex is createdfor application in educational process during teaching of discipline "Fundamentals of algorithmization and programming" as means of debug-ging a deeperunderstanding of the processes occurring in the computer, improvement of logic of writing of programs.The article considers the purpose of the program-methodological complex “Video Interpreter for searching and sorting algorithms” and the integrated environment of the course “Fundamentals of Algorithms and Programming” are described.The use of the program-methodological complex "Video Interpreter" in the educational process allows to organize at a high level students' educational and research activities; to activate students' independence in mastering knowledge; reduce the time needed to set up the program;accelerate the develop-ment of students' logical thinking.